The effectiveness of kinesiology taping on dysphagia in brain tumor survivors after neurosurgery: study protocol for a pilot randomized controlled trial - Fernandes, Júlio Belo; Monteiro, Leonor; Costa, Abílio; Gonçalves, Ana Sofia; Dean, John; Família, Carlos; Domingos, Josefa; Godinho, Catarina (Frontiers in Medicine, 2025)
Dysphagia is a common complication in brain tumor survivors, either as a direct symptom of the tumor or a result of neurosurgery. With improved survival rates, the need for effective rehabilitation strategies is more crucial than ever. Kinesiology taping has shown promise in dysphagia rehabilitation for stroke patients, but its potential in brain tumor survivors is largely unstudied and represents a significant research opportunity. This pilot study aims to assess feasibility and gather preliminary data on the impact of kinesiology taping, in addition to standard dysphagia care, on improving swallowing function in brain tumor survivors post-neurosurgery. This 1:1 parallel-group randomized controlled trial will recruit 62 brain tumor survivors with oropharyngeal dysphagia from a Neurosurgery Inpatient Unit in Portugal. Participants will be randomized into two groups: the control group, receiving standard dysphagia care, and the experimental group, receiving kinesiology taping applied to the suprahyoid muscles in addition to standard care. The intervention will last 15 sessions over 4 weeks. Primary outcomes will be assessed using the FEES Penetration-Aspiration Scale, Gugging Swallowing Test (GUSS), Dysphagia Handicap Index (DHI), and Functional Oral Intake Scale (FOIS). This study will evaluate the efficacy of kinesiology taping as a supplementary therapy for dysphagia rehabilitation in brain tumor survivors. The potential improvements in clinical care and patient outcomes are significant, reinforcing the importance of this research in enhancing the quality of life for these survivors.